(untitled) - Rosenthal, Robert (Boston, 2008)
This classic advanced undergraduate/graduate text in research methods requires statistics as a prerequisite. The first half of the text concentrates on research methods and the second half introduces students to advanced statistical procedures
Keywords: Psychology; Research,Methodology